Perception of generation X and Z teachers on post-COVID-19 media education at a public university in Tacna - Peru - Rozas Flores, Maria Ruth (2024)
This study explores the perception of post-COVID-19 media education among Generation X and Y teachers at a public university in Tacna, Peru. A qualitative approach was used with semi-structured interviews with eight teachers. The interviews were analyzed by thematic coding following the guidelines of the ALFAMED Curriculum. Teachers highlighted the importance of media education for the development of digital competencies and media literacy in the post-COVID-19 context, highlighting the need to improve digital security and privacy. Perceptions included concerns about safe data handling and protection against cyber threats, as well as ethical and responsible use of ICTs. Teachers perceive media education as essential to face the challenges of the digital environment and consider that the pandemic accelerated the need to integrate ICTs in education.